Allelopathic potential of ethanolic extract and its fractions from leaves of Geonoma schottiana Mart. - Gomes, Alessandro Bermudes; Corte, Viviana Borges; Farias, Carine Coneglian de; Rodrigues Filho, Josinei; Perini , Flávio Mauricio; Mariquito, Anderson; França, Hildegardo (Comunicata Scientiae, 2024)
Geonoma schottiana Martius (Arecaceae) is an understory palm species widely distributed in Brazil. The objective of this work was to determine the allelopathic potential of Geonoma schottiana leaf extract and its fractions of different polarities and evaluate in vitro and in vivo antioxidant activities. The germination of seeds of Lactuca sativa and Panicum maximum was tested using ethanolic leaf extract and its hexane, dichloromethane, ethyl acetate, and butanol fractions. In vitro antioxidant tests were performed through the DPPH, ABTS, FRAP, and molybdenum tests, whereas the SOD, CAT, and POX enzymatic tests were used to evaluate in vivo antioxidant activity. Chemical analyses were performed through phytochemical screening of the main groups of secondary metabolites by thin-layer chromatography and quantification of the total contents of phenolics, tannins, and flavonoids. The hexane and butanol fractions had allelopathic effects on P. maximum and low activity on L. sativa. The ethyl acetate fraction presented higher antioxidant activity in the DPPH test, whereas butanol presented higher antioxidant activity in the ABTS test. The most active fractions in terms of allelopathic effect interfered with the increases in the production of SOD and POX enzymes. The most polar fractions had higher contents of phenolic compounds. All analyzed chemical groups were found in the phytochemical screening, except the anthracene group.